MOTIVASI, KOMUNIKASI DAN SEMANGAT KERJA PEGAWAI - Freitas Belo, Maria Imaculada (Jurnal Ilmu Administrasi Negara, 2014)
Motivation, Communication and Employee Morale. This study aims to determinethe effect of motivation and communication on employee morale Kupang District Office. Studypopulation was all employees as well as the sample (census), which amounts to as many as36 people. Data collection techniques using koesioner, interviews and observations. Data wereanalyzed using simple correlation. The results showed that the partially and simultaneously, theinfluence of motivation and communication on employee morale is positive and significant. Theresults of the analysis coefficient determinant (R2) indicates that the contribution of variablemotivation and communication on employee morale sizeable 73.6% and the remaining 26.4% isinfluenced by other variables. The role of communication between the leadership of subordinatevariables is an important variable in improving employee morale.Keywords: motivation, communication, morale, leadership.